Digital experiments in aikido (2006)
Adaptive Perception presents "Digital Experiments in Aikido." This DVD documents our use of digital motion capture technology with Aikido and presents novel computer generated animations based on the results. The first section details the process from motion capture session to final animation. The bulk of the video consists of 5 categories of visualizations of the recorded techniques.